2017
DOI: 10.1111/pde.13064
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Juvenile Myelomonocytic Leukemia, Juvenile Xanthogranulomas and Neurofibromatosis Type 1: Case Report and Review of the Literature

Abstract: The occurrence of juvenile myelomonocytic leukemia (JMML), juvenile xanthogranuloma (JXG), and neurofibromatosis type 1 (NF1) together is relatively rare. Approximately only 20 cases have been reported in the literature. It is debated whether children with NF1 and JXG are at higher risk of developing JMML than children with NF1 alone. We present the case of a boy primarily diagnosed with NF1 with coexisting JXG who developed JMML at the age of 22 months. The clinical course from initial presentation to final d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 48 publications
(61 reference statements)
0
19
0
Order By: Relevance
“…JXG has been associated with neurofibromatosis type 1 (NF1), and it has been suggested that risk of developing juvenile myelomonocytic leukemia is 20‐30 times as great in patients with NF1 and multiple JXGs than in those with NF1 without JXG, although a recent study concluded that JXG lesions are common in NF1 but not associated with greater risk of malignancy …”
Section: Introductionmentioning
confidence: 99%
“…JXG has been associated with neurofibromatosis type 1 (NF1), and it has been suggested that risk of developing juvenile myelomonocytic leukemia is 20‐30 times as great in patients with NF1 and multiple JXGs than in those with NF1 without JXG, although a recent study concluded that JXG lesions are common in NF1 but not associated with greater risk of malignancy …”
Section: Introductionmentioning
confidence: 99%
“…Concurrent eruptive JXG with café‐au‐lait spots has been reported, which may be associated with NF1 mutations and NF1 as a clinical diagnosis 7,14‐17 . Although an increased risk of juvenile myelocytic leukemia in patients with JXGs and NF1 mutations has been reported, 6‐8,15 none of the patients in our study with eruptive JXG developed signs or symptoms of hematologic disorders during the period of clinical follow‐up.…”
Section: Discussionmentioning
confidence: 52%
“…The association of juvenile xanthogranuloma (JXG) and juvenile myelomonocytic leukaemia (JMML) has been described in approximately 20 cases in the literature 1‐3 ; however, the pathogenesis underlying the concomitant presentation has never been elucidated in detail. We present the case of a child who developed JXG at the age of 3 months, and 23 months later he was diagnosed with JMML harbouring a somatic PTPN11 p.E76K mutation.…”
Section: Figurementioning
confidence: 99%